The effect of board diversity on capital structure: an empirical study from the UK - Elmoursy, Hanan Mohamed (AUC Knowledge Fountain, 2020)
The main objective of this research is to examine the effect of main determinants of capital structure and board composition on capital structure decision for the UK companies on the London Stock and Exchange (LSE) during the period of 1999 - 2016. The sample of this study consists of 2175 companies in the UK with 39150 observations in UK where there are 644 companies in the MAIN market and 1528 companies in the AIM market. To the best of my knowledge, the contribution of this research could be summarized in three folds. First, this research investigates and explores the effect of some firm determinants on capital structure on companies listed in the London Stock Exchange (LSE) for both markets; MAIN and AIM. Second, very few literatures discussed the effect of board composition on capital structure, especially the effect of board diversity. This thesis focuses on the effect of executive and non-executive board members for all of the following board diversity; females on board, board age, board education, and board nationality. Third, this is the first study that takes into consideration the state of the economy, market returns, by using regime switching techniques. This has been fulfilled by exploring the effect of board diversity on capital structure using two conditions; the high (good) state of the financial market and the low (bad) state of the financial market. This research provides evidence for the board characteristics and their effect on capital structure through the following results. Board size was found to have a significant positive relationship with the decisions related to the amount of debt financing in the MAIN market in all market states. board independence results in this research was found to be negatively significant on debt financing in the MAIN market in all market states. For the board diversity, executive females on board are found negative and significant to debt financing in the MAIN market in all market states apart from the bad market. Age of executives as one of the board characteristics discussed in this research was found to have a negative significant relationship in the MAIN market in all states. Finally, the nationality of executive directors was found significant with a negative relation to capital structure in the MAIN market in all its states while the nationality of non-executive members was found significant with a negative sign in the MAIN market in all the market states apart from the bad market.